Study of Building Techniques and Deterioration Phenomena of Salty Limestone in Archaeological Buildings Applied on Oracle Temple in Siwa Oasis - Mahmoud Abdel Hafiz; Ali Abdel-Motelib; Rabea Radi Abdel Kader (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Archaeological buildings are exposed to many factors of damage to the surrounding environment, especially in Siwa Oasis, where the Temple of Oracle of Alexander the Great or the so-called Temple of Amun. It was made of salty limestone, which was examined by a scanning electron microscope (SEM), the examination showed the extent of the weakness and deterioration of the condition of the stone. The analysis was also done by X-ray fluorescence. It was found that the proportions of chlorine, sodium and potassium elements were high, which means the presence of halite (NaCL) and potassium chloride (KCL) salts among the components of the stone beside calcium carbonates CaCO3 (calcite), also, monitoring and study of the most important deterioration aspects to the temple that threaten its security and safety were conducted, in preparation for the development of a controlled treatment plan on scientific bases.